Negosiasi sebagai Alternatif dalam Manajemen Konflik di Lembaga Pendidikan - Aulia, Dini Silmy; Julaiha, Siti; Sudadi, Sudadi (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
Negotiation is a form of conflict management that provides a forum for resolving conflicts that can satisfy parties and build opportunities by establishing stronger relationships. However, awareness of the importance of negotiation is still low, even though negotiation skills, especially for students, prepare themselves to face various kinds of conflicts in the outside world. Therefore, this research explains Negotiation, types of Negotiation, Negotiation skills, and key Negotiation factors. This research uses a library research method by collecting books, previous research and articles related to Conflict Management and Negotiation. The results show that negotiation is a process of resolving problems between two or more parties, where the problem arises on the basis of different points of view which are then united in one common agreement. Negotiation types are divided into distributive and integrative. Negotiation skills by separating feelings, focusing, collecting options, and assessing objectives. Key factors through various self-skills. And the implementation of Negotiation is an effective alternative in resolving conflicts that occur in Educational Institutions, whether or not there is a mediator, both conflicts related to the learning process to conflicts over Educational Institution policies.